Facile Fabrication of Large‐Area Atomically Thin Membranes by Direct Synthesis of Graphene with Nanoscale Porosity. Issue 49 (9th October 2018) - Kidambi, Piran R.; Nguyen, Giang D.; Zhang, Sui; Chen, Qu; Kong, Jing; Warner, Jamie; Li, An‐Ping; Karnik, Rohit
Abstract: Direct synthesis of graphene with well‐defined nanoscale pores over large areas can transform the fabrication of nanoporous atomically thin membranes (NATMs) and greatly enhance their potential for practical applications. However, scalable bottom‐up synthesis of continuous sheets of nanoporous graphene that maintain integrity over large areas has not been demonstrated. Here, it is shown that a simple reduction in temperature during chemical vapor deposition (CVD) on Cu induces in‐situ formation of nanoscale defects (≤2–3 nm) in the graphene lattice, enabling direct and scalable synthesis of nanoporous monolayer graphene. By solution‐casting of hierarchically porous polyether sulfone supports on the as‐grown nanoporous CVD graphene, large‐area (>5 cm 2 ) NATMs for dialysis applications are demonstrated. The synthesized NATMs show size‐selective diffusive transport and effective separation of small molecules and salts from a model protein, with ≈2–100× increase in permeance along with selectivity better than or comparable to state‐of‐the‐art commercially available polymeric dialysis membranes. The membranes constitute the largest fully functional NATMs fabricated via bottom‐up nanopore formation, and can be easily scaled up to larger sizes permitted by CVD synthesis. The results highlight synergistic benefits in blending traditional membrane casting with bottom‐up pore creation during graphene CVD for advancing NATMs toward practical applications. Abstract : Facile fabrication of large‐area atomically thin membranes by bottom‐up synthesis of nanoporous monolayer graphene is reported. A simple reduction in graphene growth temperature enables facile synthesis of nanoporous graphene. By solution‐casting a hierarchically porous support on the as‐grown nanoporous graphene, large‐area (>5 cm 2 ) nanoporous atomically thin membranes for dialysis applications are demonstrated.